Transport simulations of pre-thermal quench shattered pellet injection in ITER: code verification and assessment of key trends. (1st October 2022) - Matsuyama, A; Hu, D; Lehnen, M; Nardon, E; Artola, J
Abstract: The material assimilation of the shattered pellet injection (SPI) in the pre-thermal quench phase in ITER is studied numerically by means of one-dimensional (1D) transport simulations. Such a simplified 1D approach is useful to perform extensive and systematic studies of key engineering parameters to optimize the ITER Disruption Mitigation System. The simulation results are compared with two-dimensional (2D) axisymmetric simulations by the nonlinear magnetohydrodynamic code JOREK for 5 % neon/95 % hydrogen SPI in the 15 MA hydrogen L-mode discharge to clarify the characteristics of SPI assimilation that can be analyzed within the range of the 1D model. Reasonable agreement between the 1D SPI simulation by the INDEX code and the 2D simulations by the JOREK code is found for total ablation rates, the radiation power, and the density and temperature profile evolution. The key process that was studied with the transport code is the onset of the radiative cold front that destabilizes the plasma current profiles. The injection parameters for the neon mixed hydrogen SPI are widely scanned to identify the timescale for the radiative cold front to form. Depending on the relative velocity of the cold front and the SPI fragments, the plasma cooling process can differ significantly. SPI with high injection velocities and large shard sizes results even in an inside-out plasma cooling that leads to hollow temperature profiles in the simulations reported here.